A libertação dos egípcios por mulheres em diálogo: estudo exegético de Êxodo 3,21-22; 11,2-3; 12,35-36 - Paula, Patricia Carneiro de (2021)
This dissertation presented here is aimed at the exegetical study of Exodus 3:21-22, 11:2-3 e 12:35-36. For that purpose, was performed the delimitation, segmentation an translation of the texts originally in Hebrew to the Portuguese, as well as linguistic and literary studies, since the Bible presents itself as literature, with morphological and syntactic analysis, in order to favor the exact understanding of the biblical text, with the recognition of stylistic elements and a narrative analysis. Even, there was a need to investigate the historicalcultural context and carry out a theological reflection promoted by the narratives, especially because of the active participation of women in the process of freeing people. The study is justified since the origins and foundation of the Christian faith is found in the Bible and, thereby, the methodology of biblical exegesis was applied through a synchronic reading, with the linguistic-literary study and the historical-geographical-cultural context, from both the narrated world and the world of authors; study of theological reflection promoted by the literary unit to be studied, with the consequent updating of the models of faith and behavior favored by the biblical narrative